Reconstructing Integrative Islamic Economics: Imam Mālik’s Substantive Legal-Economic Framework in al-Muwaṭṭaʾ and Its Relevance for Contemporary Plural Legal System - Murtadho, Ali; Mujibatun, Siti; Mohamad, Maizatul Saadiah (Universitas Negeri Semarang, 2025)
Islamic economics integrates normative ethical principles with empirical realities, emphasizing justice (ʿadl), welfare (maṣlaḥah), and holistic prosperity (falāḥ). In contrast to conventional economics, which often detaches value judgments from analysis, Islamic economics seeks moral coherence in practice. This study explores the integrative economic thought of Imam Mālik ibn Anas (93–179 AH / 711–795 CE) as articulated in al-Muwaṭṭaʾ, a foundational legal text notable for embedding legal rulings within real economic contexts. Mālik’s jurisprudence reflects an empirical-normative synthesis, operationalizing Sharīʿah ethics in economic transactions through principles such as value equivalence, transparency, risk-sharing, and avoidance of speculation (gharar, maysir). The study employs a multidisciplinary qualitative methodology grounded in textual analysis to examine how al-Muwaṭṭaʾ provides a coherent framework for value-based economics. It investigates key legal-economic themes including contract ethics, distributive justice, monetary stability, and risk management. Findings suggest that Mālik’s integrative approach offers a corrective paradigm for contemporary Islamic finance, which often privileges legal form over economic substance. His model supports a shift toward ethical substance aligned with maqāṣid al-sharīʿah, offering relevance not only within Muslim-majority societies but also in pluralistic legal systems. This study contributes to the development of Islamic economic thought by advocating a paradigm rooted in ethical authenticity, responsive governance, and cross-cultural applicability—thereby advancing a more substantive and policy-relevant Islamic economic discourse.